2006
DOI: 10.1063/1.2384776
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation oscillations in a capacitive discharge chamber connected to a peripheral grounded chamber

Abstract: We have observed relaxation oscillations in an argon capacitive discharge connected to a peripheral grounded chamber through a slot with dielectric spacers. The oscillations, observed from time-varying optical emission of the main discharge chamber, show, for example, a high frequency (∼40kHz) relaxation oscillation at 100mTorr, with absorbed power near that for peripheral breakdown, and a low frequency (∼3Hz) oscillation, at higher absorbed power. The high frequency oscillation is found to ignite a plasma in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…It forms one or more striations, and the striations can be either stagnant or continuously circling around the grounding stage with a non-constant frequency. Such a phenomenon has been reported 16) and was termed plasmoid in some literature. 12) Although the rf voltage above which this breakdown occurs is reproducible, the non-uniform plasma appearance in the peripheral region and the position where the striations are located do not behave in a controllable manner.…”
Section: Appearance and Current-voltage Characteristicsmentioning
confidence: 92%
See 2 more Smart Citations
“…It forms one or more striations, and the striations can be either stagnant or continuously circling around the grounding stage with a non-constant frequency. Such a phenomenon has been reported 16) and was termed plasmoid in some literature. 12) Although the rf voltage above which this breakdown occurs is reproducible, the non-uniform plasma appearance in the peripheral region and the position where the striations are located do not behave in a controllable manner.…”
Section: Appearance and Current-voltage Characteristicsmentioning
confidence: 92%
“…The unintentional breakdown in this region has been reported by several researchers. [14][15][16] Lieberman et al reported the peripheral region breakdown observed in a parallel-plate, capacitively coupled plasma chamber consisting of a peripheral region connected to the main chamber through an annular dielectric slot. Experimental work and numerical simulation revealed that this peripheral region breakdown is greatly influenced by the potential of the bulk plasma adjacent to the peripheral region as well as the diffusion of the charged species from the bulk plasma to the peripheral region.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We determined the mode characteristics with Maxwell equations, of which the detailed discussion may be found in our previous paper. [5]…”
Section: Electromagnetic Analysis Of the Slot Impedancementioning
confidence: 99%
“…We determined the mode characteristics with Maxwell equations detailed discuss in our previous paper. [5] Fig. 4.…”
mentioning
confidence: 99%